2021
DOI: 10.1007/s00127-021-02098-6
|View full text |Cite
|
Sign up to set email alerts
|

The genetic background of the associations between sense of coherence and mental health, self-esteem and personality

Abstract: Purpose Sense of coherence (SOC) represents coping and can be considered an essential component of mental health. SOC correlates with mental health and personality, but the background of these associations is poorly understood. We analyzed the role of genetic factors behind the associations of SOC with mental health, self-esteem and personality using genetic twin modeling and polygenic scores (PGS). Methods Information on SOC (13-item Orientation of Life Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Sense of coherence, referring to a consistent but dynamic feeling of confidence, defined as the belief that life is comprehensive, manageable and meaningful, was operationalised as a resilience phenotype in three studies ( 121 123 ). The first GWA analysis recently conducted for SOC yielded a significant association, rs74920024 on chromosome 2 ( 282 ). The association locus is close to Glycerol-3-Phosphate Dehydrogenase 2 ( GPD2) , a gene encoding a protein that localizes to the inner mitochondrial membrane and is responsible for the conversion of glycerol-3-phosphate to dihydroxyacetone phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…Sense of coherence, referring to a consistent but dynamic feeling of confidence, defined as the belief that life is comprehensive, manageable and meaningful, was operationalised as a resilience phenotype in three studies ( 121 123 ). The first GWA analysis recently conducted for SOC yielded a significant association, rs74920024 on chromosome 2 ( 282 ). The association locus is close to Glycerol-3-Phosphate Dehydrogenase 2 ( GPD2) , a gene encoding a protein that localizes to the inner mitochondrial membrane and is responsible for the conversion of glycerol-3-phosphate to dihydroxyacetone phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that social anxiety is related to variability in the sensitivity of affective brain-behavioral systems that mediate personality (Kimbrel, 2008). Indicators of personality, self-esteem, and mental health share a substantial proportion of genetic variation (Silventoinen et al, 2022). The present study examines the strength of the relationships between biologically defined personality constructs, self-esteem, and social anxiety.…”
mentioning
confidence: 91%
“…Furthermore, when assessing PSYCA, personality factors and ontological beliefs seem to have a greater influence than demographical factors like gender, age, or social group (34). Personality factors that are known to be associated with mental health impairments in general, such as the level of structural integration (35), attachment style (36), and sense of coherence (37), might therefore also be of interest when trying to understand PSYCA. While a substantive body of research on the interplay of personality factors and pro-environmental behavior or climate change denial exists (38,39), the authors found no conclusive literature on the relationship of personality factors and PSYCA.…”
Section: Introductionmentioning
confidence: 99%